Fast Stereolithography Printing of Large‐Scale Biocompatible Hydrogel Models. Issue 10 (15th February 2021) - Anandakrishnan, Nanditha; Ye, Hang; Guo, Zipeng; Chen, Zhaowei; Mentkowski, Kyle I.; Lang, Jennifer K.; Rajabian, Nika; Andreadis, Stelios T.; Ma, Zhen; Spernyak, Joseph A.; Lovell, Jonathan F.; Wang, Depeng; et al.
Abstract: Large size cell‐laden hydrogel models hold great promise for tissue repair and organ transplantation, but their fabrication using 3D bioprinting is limited by the slow printing speed that can affect the part quality and the biological activity of the encapsulated cells. Here a fast hydrogel stereolithography printing (FLOAT) method is presented that allows the creation of a centimeter‐sized, multiscale solid hydrogel model within minutes. Through precisely controlling the photopolymerization condition, low suction force‐driven, high‐velocity flow of the hydrogel prepolymer is established that supports the continuous replenishment of the prepolymer solution below the curing part and the nonstop part growth. The rapid printing of centimeter‐sized hydrogel models using FLOAT is shown to significantly reduce the part deformation and cellular injury caused by the prolonged exposure to the environmental stresses in conventional 3D printing methods. Embedded vessel networks fabricated through multiscale printing allows media perfusion needed to maintain the high cellular viability and metabolic functions in the deep core of the large‐sized models. The endothelialization of this vessel network allows the establishment of barrier functions. Together, these studies demonstrate a rapid 3D hydrogel printing method and represent a first step toward the fabrication of large‐sized engineered tissue models. Abstract : This work presents the development of fast hydrogel stereolithography technology (FLOAT) for the fabrication of large‐sized biocompatible hydrogel models. The high printing speed of the FLOAT significantly reduces environmental stress‐induced cellular injuries. The perfusable vessel networks enabled by the multiscale printing capability allows maintenance of high cellular viability and metabolic functions in the core of the large‐sized models.